Municipal Register of the City of Haverhill 155 (1897) - (:unkn) unknown (My University, 1897)
Ch. 40, § 1: No person shall fire or discharge any gun, pistol, revolver or other fire-arms within the compact part of the city, under a penalty for every such offence, not exceeding twenty dollars; provided, however, that this section shall not apply to the use of such weapons at any military exercise or review, or in the lawful defence of the person, family, or property of any citizen.
Keywords: DISCHARGE